Pengaruh E-Service Quality Terhadap Kepuasan Pelanggan Di Shofee (Studi Pada Mahasiswa FEB UISU Prodi Manajemen Angkatan 2020) - Ayusana, Sri; Helmi, Tengku Ahmad; Yudha, Tri Kartika (Universitas Islam Islam Sumatera Utara, 2023)
This study aims to determine the Effect of E-Service Quality on Customer Satisfaction at Shopee (study on FEB UISU students, Management Study Program class of 2020). The population of this study were 160 FEB UISU management study program students using the Slovin sampling formula, obtained a sample size of 62 samples and allocated to each stratum using the proportional random sampling formula. The data was analyzed using the SPSS 20 program. Based on the results of the study, it can be concluded that E-Service Quality (Efficiency, Reliability, Fulfillment, Privacy, Responsiveness, Compensation, Contact Communication) simultaneously has a significant effect on Customer Satisfaction